Optimal Antiplatelet Therapy in Moderate to Severe Asymptomatic and Symptomatic Carotid Stenosis: A Comprehensive Review of the Literature. (February 2019) - Murphy, Stephen J.X.; Naylor, A. Ross; Ricco, Jean-Baptiste; Sillesen, Henrik; Kakkos, Stavros; Halliday, Alison; de Borst, Gert J.; Vega de Ceniga, Melina; Hamilton, George; McCabe, Dominick J.H.
Abstract : Objectives: Carotid stenosis patients are at risk of vascular events despite antiplatelet therapy. Data on prescribed antiplatelet regimens have not been comprehensively collated from trials to guide optimal therapy in this population. Methods: This review was conducted in line with the current Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Medline, Ovid, Embase, Web of Science, and Google Scholar from 1988 to 2018 were searched using the search terms "carotid stenosis", "asymptomatic", "symptomatic", "antiplatelet", and "anti-platelet" to identify randomised trials in patients with asymptomatic or symptomatic extracranial moderate–severe carotid stenosis on any form of antiplatelet therapy in which vascular events and pre specified composite outcome events were reported. Results: Twenty-five studies were judged eligible for inclusion. Data from one randomised controlled trial showed no significant difference in benefit with aspirin versus placebo in asymptomatic carotid stenosis, but it is still reasonable to recommend aspirin (81–325 mg daily) for prevention of vascular events in these patients. Low to medium dose aspirin (81–325 mg daily) is superior to higher doses (>650 mg daily) at preventing recurrent vascular events in patients undergoing endarterectomy. Data from endovascular treatment (EVT) trials support peri-procedural treatment of asymptomatic and symptomatic patients with 81–325 mg of aspirin daily. The use of peri-procedural aspirin–clopidogrel in patients undergoing EVT is based on one pilot trial, but appears safe. Short-term aspirin–dipyridamole or aspirin–clopidogrel treatments are equally effective at reducing micro-embolic signals on transcranial Doppler ultrasound in patients with ≥50% symptomatic carotid stenosis. There is insufficient evidence to recommend routine aspirin–clopidogrel combination therapy to reduce the risk of recurrent clinical ischaemic events in patients with symptomatic moderate–severe carotid stenosis. Conclusions: This comprehensive review outlines an evidence based approach to antiplatelet therapy in carotid stenosis patients. Future trials should randomise such patients to receive different antiplatelet regimens to assess their efficacy and safety and to optimise peri-procedural and long-term preventive treatment in this patient cohort.